Exploring Vocabulary Use During English Writing Among First-Year EFL Students: A Qualitative Study - Riya Risqi Setyaningrum; Hariyanto; Chusnu Yuli Setyo; Neng Surti (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2026)
Vocabulary use is essential in English writing because learners must make continuous lexical decisions to express ideas accurately and appropriately. Previous studies have primarily examined vocabulary mastery, lexical diversity, and writing quality as measurable outcomes, providing limited insight into how learners use vocabulary during the writing process. This study explored how first-year EFL students used vocabulary while composing English descriptive texts. A qualitative case study was conducted with 30 first-year English Education students at Universitas Islam Lamongan, Indonesia. Data were collected through descriptive writing tasks, think-aloud protocols, and stimulated recall interviews, and analyzed using Reflexive Thematic Analysis. Following preliminary coding of all writing products, six information-rich cases were purposively selected for in-depth analysis. The findings revealed that vocabulary use was a dynamic and recursive process involving five interconnected stages: lexical retrieval, lexical search, lexical selection, lexical evaluation, and lexical revision. The integration of multiple data sources showed that students continuously negotiated between their lexical knowledge, cultural meanings, communicative intentions, and contextual demands while composing texts. These findings reconceptualize vocabulary as a strategic process rather than merely a linguistic product. The study suggests that vocabulary instruction should emphasize process-oriented lexical strategies, including searching, evaluating, and revising vocabulary, to foster more effective writing development in EFL contexts.